Genus Camptocercus (Cladocera: Anomopoda: Chydoridae) in North America - SINEV, ARTEM Y. (Zootaxa, 2018)
Genus Camptocercus is represented in North America by four species. Camptocercus rotundus Herrick, 1882 is proved to be a valid species and is redescribed here. C. rotundus differs from its sibling species, neotropical C. dadayi Stingelin, 1913, in morphology of the postabdominal claw, presence of posteroventral denticles on valves, and morphology of the male postabdomen. C. rotundus is distributed in South Canada and North USA from Pacific to Atlantic coast, whereas C. dadayi is found in Mexico and South-East USA. C. oklahomensis Mackin, 1930 is found in Central USA. C. streletskaye Smirnov, 1998, previously known from Chukotka and Magadan Area of Russia, was found in Alaska for the first time.